(untitled) (Docentes 2.0 Journal, 2026)
Learning English in basic education is a key pillar for social, economic, and cultural development in globalized contexts. Linguistic proficiency expands academic, professional, and intercultural opportunities. The objective of this study was to analyze the challenges and global perspectives of teaching English in basic education, focusing on sustainable development principles. This essay follows the critical-social paradigm, uses a deductive method, takes a qualitative approach, and adopts an analytical-documentary type with a topical narrative design. The study covers recent scientific literature and international educational policy documents. Documentary review was used, with a categorical analysis matrix as the main instrument to compare educational policies and pedagogical strategies in different contexts. The analysis showed that integrating English in basic education requires more than following norms. It needs effective coordination among public policies, teacher training, and the use of educational technologies. The study found both progress and limitations in countries like Mexico, Brazil, Nepal, Finland, and Rwanda, connected to structural, sociocultural, and technological factors. Strengthening English instruction from an early age is key to equity, competitiveness, and holistic development. However, success depends on clear links between curricular design, local conditions, and instructional strategies